Metamaterial structure with strength and toughness capable of being cooperatively regulated and controlled and bionic biphase design method thereof

By combining bionic Bouligand structure and biphase design, a metamaterial structure with adjustable interlayer angle and material proportion is constructed, which solves the problem of traditional materials decreasing toughness when increasing strength, and achieves coordinated regulation between strength and toughness.

CN119558128AActive Publication Date: 2025-03-04WUHAN UNIV OF TECH

Patent Information

Application Number
CN202411631280.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-04
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

While increasing the strength, existing materials often lead to a decrease in toughness, making it difficult to achieve coordinated regulation between strength and toughness.

Method used

Using a method of combining bionic Bouligand structure with biphasic design, a Bouligand spiral stacked structure composed of soft and hard phase materials is constructed. By adjusting the interlayer angle and material proportion, strength and toughness can be coordinated.

Benefits of technology

By fully utilizing mechanisms such as interlayer coupling, stress transmission, crack propagation and interface energy dissipation, the designed metamaterial structure can significantly improve toughness while maintaining strength, achieving coordinated regulation between strength and toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119558128A_ABST
    Figure CN119558128A_ABST
Patent Text Reader

Abstract

The invention relates to a metamaterial structure with strength and toughness capable of being cooperatively regulated and controlled and a bionic biphase design method of the metamaterial structure, the metamaterial is of a Bouligand spiral stacking structure formed by combining soft-phase material rods and hard-phase material rods, the included angle between the two layers in the rod direction is 7.5-30 degrees, and the number ratio of the hard-phase material rods to the soft-phase material rods in the same layer is 1: 3-3: 1. According to the invention, a bionic structure in nature is combined with a biphase design, and a plurality of synergistic mechanisms in energy dissipation such as remarkable interlayer coupling, effective stress transfer, distortion crack propagation, interface energy dissipation and crack path guidance between different phases are fully utilized, so that a bionic biphase bourgand configuration is innovatively designed; the innovation and development of a bionic structure material design thought are promoted, a thought is provided for solving the conflict between strength and toughness, and a solution is provided for combination of rigid protection and flexible protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metamaterial composite materials, and more specifically, to a bionic dual-phase design method for a metamaterial structure capable of synergistically regulating strength and toughness. Background Art

[0002] Porous materials have attracted widespread attention due to their excellent mechanical properties and multifunctional characteristics. They have shown promising applications in lightweight load-bearing components, heat exchangers, and other fields. For centuries, researchers have been committed to improving the strength of materials. However, material strengthening is usually accompanied by a sharp drop in toughness, resulting in low toughness of high-strength materials and low strength of high-toughness materials. Therefore, the traditional method of developing high-strength and high-toughness materials has evolved into seeking a balance between strength and toughness.

[0003] Nature provides design references and inspiration for the synergistic balance between strength and toughness. Among them, the bionic Bouligand structure is the mechanical basis for the survival of many organisms and has also been a research hotspot in recent years. This configuration increases the crack surface area, and the modulus oscillations it produces also enhance crack torsion. It exhibits good performance characteristics through significant interlayer coupling, effective stress transfer, and torsional crack propagation mechanisms. Although the mechanism in the bionic Bouligand structure has been revealed, due to the relatively simple material composition, the interface energy dissipation has not been fully utilized, and the design based on this structure has the possibility of further breakthroughs. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a metamaterial structure with coordinated regulation of strength and toughness and a bionic two-phase design method thereof, which combines the bionic Bouligand structure with the two-phase design to make full use of interface energy dissipation.

[0005] The technical solution adopted by the present invention to solve its technical problem is: constructing a metamaterial structure with coordinated regulation of strength and toughness, wherein the metamaterial is a Bouligand spiral stacking structure composed of soft phase material rods and hard phase material rods, the angle between the two layers of rod directions is 7.5° to 30°, and the ratio of the number of hard phase material rods to the number of soft phase material rods in the same layer is 1:3 to 3:1.

[0006] According to the above scheme, the soft phase material is thermoplastic polyurethane, and the hard phase material is polylactic acid.

[0007] The present invention also provides a bionic dual-phase design method for a metamaterial structure whose strength and toughness can be coordinated and regulated, comprising the following steps:

[0008] S1. Combining the bionic Bouligand structure with the dual-phase design to obtain a dual-phase bionic Bouligand structure;

[0009] S2. Perform parametric design of the interlayer angle and material ratio of the configuration; the interlayer angle is the angle between the rod directions of two layers, and the material ratio is the ratio of the number of rods of two materials in one layer. During the parametric design, the angle range is controlled within 7.5° to 30°, and the ratio of hard phase to soft phase materials is controlled within 1:3 to 3:1;

[0010] S3. Conduct experimental verification, numerical simulation verification and practical application verification on the configuration.

[0011] According to the above scheme, in step S1, a two-phase bionic Bouligand structure sample is prepared by molten filament printing. The sample is printed by a dual-nozzle printer. The left and right nozzles of the printer print different materials simultaneously, and finally a two-phase bionic Bouligand structure is manufactured.

[0012] According to the above scheme, the steps of experimental verification in step S3 include:

[0013] S31A, 3D modeling and molten filament manufacturing of the designed configuration;

[0014] S32A, quasi-static compression, dynamic compression and three-point bending tests were performed on the configuration;

[0015] S33A, record and export the experimental results required for analysis through the equipment.

[0016] According to the above scheme, the step of performing numerical simulation verification in step S3 includes:

[0017] S31B, obtain the material parameter constitutive model of the soft and hard dual-phase materials; for the quasi-static compression model, the material needs to be subjected to a uniaxial tensile test, and the material constitutive model used in the dynamic compression model needs to be subjected to a dynamic mechanical analysis of the material;

[0018] S32B, perform 3D modeling and meshing of the configuration under different working conditions of quasi-static compression, dynamic compression and three-point bending, and set appropriate boundary conditions;

[0019] S33B, calculate and export the results required for the experiment for analysis.

[0020] According to the above scheme, the quasi-static compression numerical simulation in step S32B includes:

[0021] Finite element software is used to simulate its quasi-static compression mechanical behavior. A quasi-static compression geometric model is established, including two rigid platens and a target specimen. Contact is applied between the rigid platens and the target specimen, and a displacement load is applied to the upper rigid platen. The lower rigid platen is fixed, and units are used to discretize the rigid platens and the structural specimen, respectively.

[0022] According to the above scheme, the dynamic compression numerical simulation in step S32B includes:

[0023] Finite element software was used to simulate its dynamic compression mechanical behavior. A full-size SHPB model was established, including the specimen, bullet, incident rod and transmission rod. Contact was imposed between the rigid platen and the target specimen, and velocity load was applied to the bullet. The bullet, incident rod and transmission rod were discretized using units, and the units of the structural specimen were the same as those during quasi-static loading.

[0024] According to the above scheme, the step of performing application verification in step S3 includes:

[0025] S31C, add a two-phase bionic Bouligand structure to the ordinary insole to design the BDBM insole; S32C, compare and calculate the impact response spectra of the BDBM insole under different parameters;

[0026] S33C, select the configuration with the best effect, place the PVDF piezoelectric film sensor between the insole and the heel, and record the dynamic real-time signal;

[0027] S34C, output signal results and analyze them.

[0028] In the bionic two-phase design method of the metamaterial structure described in the present invention, the strength and toughness can be synergistically regulated.

[0029] In the bionic two-phase design method of the metamaterial structure described in the present invention, the strength and toughness can be synergistically regulated.

[0030] The bionic dual-phase design method for the strength-toughness coordinated regulation of the metamaterial structure of the present invention has the following beneficial effects:

[0031] The present invention combines the bionic structure in nature with the two-phase design, fully utilizes various synergistic mechanisms in energy dissipation such as significant interlayer coupling, effective stress transfer, torsion crack extension, interface energy dissipation and crack path guidance between different phases, and innovatively designs a bionic two-phase bouligand configuration, promotes the innovation and development of bionic structural material design ideas, provides ideas for resolving the conflict between strength and toughness, and provides solutions for the combination of rigid and flexible protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The present invention will be further described below with reference to the accompanying drawings and embodiments, in which:

[0033] Figure 1 It is a flow chart of the bionic dual-phase design method of the present invention for synergistically regulating the strength and toughness of a metamaterial structure;

[0034] Figure 2It is a schematic diagram of the biomimetic two-phase Bouligand structure (BDBM);

[0035] Figure 3 It is a schematic diagram of the manufacturing process of the bionic two-phase Bouligand structure;

[0036] Figure 4 It is a schematic diagram of the interlayer angle and material ratio of the bionic two-phase Bouligand structure;

[0037] Figure 5 is a curve diagram of the configuration quasi-static compression test and numerical simulation results;

[0038] Figure 6 is a curve diagram of the configuration dynamic compression test and numerical simulation results;

[0039] Figure 7 It is the curve diagram of the configuration three-point bending test results and the SEM cross-sectional image;

[0040] Figure 8 This is a schematic diagram of the change in voltage signal of the BDBM insole when a person is exercising in rope skipping and running modes. DETAILED DESCRIPTION

[0041] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described in detail with reference to the accompanying drawings.

[0042] Porous materials have excellent mechanical properties and can be divided into two configurations: tensile-dominated and bending-dominated. Tensile-dominated porous materials have the characteristics of "high strength and low toughness", while bending-dominated porous materials have the characteristics of "low strength and high toughness". Strength and toughness represent the ability of materials to bear loads and resist fracture, respectively, but high strength and high toughness are often mutually exclusive. Therefore, the traditional method of developing high-strength and high-toughness materials has evolved into seeking a balance between strength and toughness.

[0043] The design criteria of this synergistically regulated strength-toughness metamaterial are as follows:

[0044] (1) Metamaterials need to fully exploit multiple synergistic mechanisms of energy dissipation, namely, significant interlayer coupling, effective stress transfer, torsional crack propagation, interface energy dissipation, and crack path guidance between different phases.

[0045] (2) Metamaterials need to seek a balance between strength and toughness.

[0046] (3) The dual-phase design of metamaterials has a soft phase and a hard phase.

[0047] Example 1

[0048] The present invention provides a metamaterial structure with coordinated controllable strength and toughness. The metamaterial is a Bouligand spiral stacking structure composed of soft phase material rods and hard phase material rods. The angle between the two layers of rods is 7.5° to 30°, and the ratio of the number of hard phase material rods to the number of soft phase material rods in the same layer is 1:3 to 3:1. Preferably, in this embodiment, the soft phase material is thermoplastic polyurethane and the hard phase material is polylactic acid.

[0049] See also Figure 1 The present invention provides a bionic dual-phase design method for a metamaterial structure that can coordinately regulate strength and toughness. The metamaterial is a Bouligand structure composed of a soft and hard dual phase. The structural design steps include:

[0050] S1. Combining the bionic Bouligand structure (BM) with the dual-phase design, a dual-phase bionic Bouligand structure (BDBM) is proposed;

[0051] S2. Parametric design of the interlayer angle and material ratio of the configuration is performed, such as Figure 4 As shown, the interlayer angle is the angle between the rod directions of the two layers, and the material ratio is the ratio of the number of rods of the two materials in one layer. During the parametric design, the angle range is controlled within 7.5° to 30°, and the ratio of hard phase to soft phase materials is controlled within 1:3 to 3:1.

[0052] S3. Conduct experimental verification, numerical simulation verification and practical application verification on the configuration.

[0053] The BDBM structure obtained by the present invention through the above-mentioned design steps can make full use of various synergistic mechanisms in energy dissipation, such as significant interlayer coupling, effective stress transfer, torsional crack propagation, interface energy dissipation and crack path guidance between different phases.

[0054] In this embodiment, the steps of performing experimental verification in step S1 include:

[0055] S11, such as Figure 2 As shown, inspired by the bionic Bouligand structure, the structure is combined with a dual-phase design, and the soft phase and the hard phase are combined to obtain a dual-phase bionic Bouligand structure (BDBM);

[0056] S12, such as Figure 3 As shown, the sample was prepared using FFF (fused filament fabrication) printing technology. The sample was printed using a dual-nozzle printer, which simultaneously prints different materials with the left and right nozzles, and ultimately a dual-phase bionic Bouligand structure can be manufactured.

[0057] In this embodiment, the steps of performing experimental verification in step S3 include:

[0058] S31A, 3D modeling and molten filament manufacturing of the designed configuration;

[0059] S32A, quasi-static compression, dynamic compression and three-point bending tests were performed on the configuration;

[0060] S33A, record and export the experimental results required for analysis through the equipment.

[0061] In some embodiments of the present invention, the numerical simulation verification of step S3 includes:

[0062] S31B, obtain the material parameter constitutive model of the soft and hard dual-phase materials. For the quasi-static compression model, the material needs to be subjected to a uniaxial tensile test, and the material constitutive model used in the dynamic compression model needs to be subjected to a dynamic mechanical analysis (DMA) of the material;

[0063] S32B, perform 3D modeling and meshing of the configuration under different working conditions of quasi-static compression, dynamic compression and three-point bending, and set appropriate boundary conditions;

[0064] S33B, calculate and export the results required for the experiment for analysis.

[0065] In some more specific embodiments of the present invention, the quasi-static compression numerical simulation of step S32B includes:

[0066] Finite element software is used to simulate its quasi-static compression mechanical behavior. A quasi-static compression geometric model is established, including two rigid plates and a target specimen. Appropriate contact is applied between the rigid plates and the target specimen, and a displacement load is applied to the upper rigid plate. The lower rigid plate is fixed, and appropriate units are used to discretize the rigid plate and the structural specimen.

[0067] In some more specific implementations of the present invention, the dynamic compression numerical simulation of step S32B includes:

[0068] Finite element software was used to simulate its dynamic compression mechanical behavior. A full-scale SHPB model was established, including the specimen, bullet, incident rod and transmission rod. Appropriate contact was applied between the rigid platen and the target specimen, and velocity load was applied to the bullet. Appropriate units were used to discretize the bullet, incident rod and transmission rod, and the units of the structural specimen were the same as those in quasi-static loading.

[0069] In this implementation, the steps of performing actual application verification in step S3 include:

[0070] S31C, add a two-phase bionic Bouligand structure to the ordinary insole to design the BDBM insole; S32C, compare and calculate the impact response spectra of the BDBM insole under different parameters;

[0071] S33C, select the configuration with the best effect, place the PVDF piezoelectric film sensor between the insole and the heel, and record the dynamic real-time signal;

[0072] S34C, output signal results and analyze them.

[0073] The bionic dual-phase design method and application effect of the above-mentioned metamaterial with coordinated strength and toughness regulation are described below through specific examples.

[0074] Example 2

[0075] See also Figure 2 , Figure 2 It is a schematic diagram of the biphasic biomimetic Bouligand structure (BDBM). Figure 2 It can be seen that, inspired by the bionic Bouligand structure, the structure is combined with the dual-phase design, and the soft phase and the hard phase are combined to obtain a dual-phase bionic Bouligand structure (BDBM), and a metamaterial with synergistically adjustable strength and toughness is obtained. The embodiment is mainly used to illustrate the bionic dual-phase design method of the above-mentioned metamaterial with synergistically adjustable strength and toughness, wherein the soft phase material is thermoplastic polyurethane (TPU) and the hard phase material is polylactic acid (PLA), and the specific steps are as follows:

[0076] (1) The original BDBM structure is designed with different interlayer angles and material ratios. The different interlayer angles include 7.5°, 15°, 22.5°, and 30°, and the different material ratios include 1:0, 0:1, 1:1, 2:1, 1:2, 3:1, and 1:3, thereby obtaining more different structural models;

[0077] (2) For the designed configuration, Figure 3 As shown, actual samples were prepared using FFF (fused filament fabrication) printing technology for experiments.

[0078] (3) Perform a quasi-static compression test on the configuration. The quasi-static compression test is performed on a universal testing machine with a certain loading speed. The engineering stress of the structure is calculated based on the compression load data obtained by the sensor, while the engineering strain is calculated based on the original displacement data of the indenter.

[0079] (4) Perform quasi-static compression numerical simulation on the configuration. Uniaxial tensile tests were performed on PLA and TPU standard dog-bone specimens, and the obtained performance curves were used as input for quasi-static compression simulation. The commercial finite element software ABAQUS / Explicit was used to simulate its quasi-static compression mechanical behavior. The experimental and numerical simulation results are shown in Figure 2. Figure 5 shown.

[0080] Depend on Figure 5From the angle effect, it can be seen that the curve trends and values ​​of the test and simulation results affected by the interlayer angle are basically consistent, which verifies that the simulation model can accurately simulate the mechanical response of the configuration under quasi-static compression. Under the influence of the angle, as the angle increases, the performance curve shows an upward trend, and the curve characteristics change from concave to convex, and the curve trends of 15°, 22.5°, and 30° are similar to the values. In addition to the interlayer angle, the material ratio is also an important parameter that affects the mechanical properties of the structure. Figure 5 It can be seen from the influence of the proportion that the higher the proportion of PLA material, the better the performance of the structure.

[0081] (5) Perform dynamic compression test on the configuration. The dynamic compression test is carried out using the SHPB experimental device. The SHPB system consists of a bullet, an incident rod, a transmission rod, and a sample sandwiched between the two rods. The bullet impacts the incident rod at a certain speed, outputs a pressure pulse, and the engineering stress-strain curve can be obtained through theoretical calculation.

[0082] (6) Perform dynamic compression numerical simulation on the configuration. For the material parameters of dynamic simulation, dynamic mechanical analysis (DMA) was performed on PLA and TPU materials, and the DMA test curve was used as the input of dynamic compression simulation. The commercial finite element software ABAQUS / Explicit was used to simulate its quasi-static compression mechanical behavior. The experimental and numerical simulation results are shown in Figure 2. Figure 6 shown.

[0083] Depend on Figure 6 It can be seen from the material influence that the curve trend and value of the test and simulation results affected by the material are basically consistent. The curve shows an upward trend and then decreases after reaching the maximum value. This is consistent with the typical curve of cellular materials under dynamic compression loading conditions, which verifies that the simulation model can more accurately simulate the mechanical response of the configuration under quasi-static compression. Figure 6 It can be seen from the influence of the interlayer angle that with the increase of the interlayer angle, the dynamic compression mechanical properties first increase and then decrease, and the performance is optimal when the interlayer angle is around 15°. Figure 6 It can be seen from the influence of the material ratio that with the increase of the PLA material ratio, the overall performance curve shows an increasing trend.

[0084] (7) Perform a three-point bending test on the configuration. Figure 5 , Figure 6 After comprehensive analysis of static and dynamic compression performance, three typical specimens, BM-P, BM-T and BDBM-15°, were selected for three-point bending tests. Figure 7 As shown by Figure 7 The curve shows that the BDBM-15° structure curve is in the middle position and has the best performance characteristics, indicating that its peak stress and peak strain are balanced. And its deformation state is more ideal, as shown by Figure 7From the SEM cross-sectional image, it can be seen that the structure is broken at the PLA material position and deformed greatly at the TPU material position. Under three-point bending, the BDBM mode shows a relatively stable deformation state with multiple synergistic mechanisms, including significant coupling between layers, effective stress transfer, torsional crack propagation, interface energy dissipation, and crack path guidance between different phases.

[0085] (8) Verification of the practical application of the BDBM structure. By comparing the shock response spectra (SRS) of the BM-P, BM-T and BDBM structures under different geometric parameters, it is found that the SRS curve of the BDBM-15° configuration is between BM-P and BM-T. Figure 5 , Figure 6 , Figure 7 The performance result curve of the BDBM mode is selected for practical application verification.

[0086] (9) BDBM insoles are carefully designed and printed for impact protection. PVDF piezoelectric film sensors are placed between the insole and the heel to record dynamic real-time signals. The changes in voltage signals under rope skipping and running exercise modes are shown in Figure 1. Figure 8 It can be observed that after adding the BDBM insole, the voltage signal amplitude decreases and the pulse width increases, indicating that the impact intensity of the athlete during rope skipping is reduced, the adaptation time is prolonged, and a satisfactory personnel protection effect is achieved.

[0087] According to the results, the strength and toughness of the metamaterial of the present invention can be synergistically regulated. The toughness is effectively increased with a small change in strength, achieving synergistic regulation of strength and toughness. This proves that the bionic dual-phase design method proposed in this patent has significant effects.

[0088] The advantages of the present invention are as follows:

[0089] 1. Under quasi-static and dynamic compression loading conditions, the internal stress of the BDBM configuration is mainly distributed along the material deformation direction, between different phase interfaces, and between different layer interfaces. A large amount of energy is dissipated at the interface, showing a significant interlayer coupling effect.

[0090] 2. In the three-point bending test, the BDBM configuration has a balance between peak stress and peak strain. And its deformation state is more ideal, with fracture at the PLA material position and large deformation at the TPU material position. In this case, the BDBM configuration exhibits a relatively stable deformation state and has multiple synergistic mechanisms, including significant coupling between layers, effective stress transfer, torsional crack propagation, interface energy dissipation, and crack path guidance between different phases.

[0091] 3. BDBM configurations with different geometric parameters have different shock response spectrum (SRS) curves and impact protection effects. After adding BDBM insoles, the voltage signal amplitude decreases and the pulse width increases, indicating that when athletes skip rope or run on gravel roads, the impact intensity is lower and the adaptation time is longer, resulting in a satisfactory personnel protection effect.

[0092] In summary, the present invention combines the bionic structure in nature with the two-phase design, fully utilizes various synergistic mechanisms in energy dissipation such as significant interlayer coupling, effective stress transfer, torsion crack extension, interface energy dissipation and crack path guidance between different phases, and innovatively designs a bionic two-phase bouligand configuration, promotes the innovation and development of bionic structural material design ideas, provides ideas for resolving the conflict between strength and toughness, and provides solutions for the combination of rigid and flexible protection.

[0093] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.

Claims

1. A metamaterial structure with coordinated strength and toughness control, characterized in that: The metamaterial is a Bouligand spiral stacking structure composed of soft phase material rods and hard phase material rods, the angle between the rod directions of the two layers is 7.5° to 30°, and the ratio of the number of hard phase material rods to the number of soft phase material rods in the same layer is 1:3 to 3:

1.

2. The strength-toughness synergistically regulated metamaterial structure according to claim 1, characterized in that: The soft phase material is thermoplastic polyurethane, and the hard phase material is polylactic acid.

3. A bionic dual-phase design method for a metamaterial structure with coordinated strength and toughness control as claimed in claim 1, characterized in that: The following steps are involved: S1. Combining the bionic Bouligand structure with the dual-phase design to obtain a dual-phase bionic Bouligand structure; S2. Perform parametric design of the interlayer angle and material ratio of the configuration; the interlayer angle is the angle between the rod directions of two layers, and the material ratio is the ratio of the number of rods of two materials in one layer. During the parametric design, the angle range is controlled within 7.5° to 30°, and the ratio of hard phase to soft phase materials is controlled within 1:3 to 3:1; S3. Conduct experimental verification, numerical simulation verification and practical application verification on the configuration.

4. The bionic dual-phase design method for a metamaterial structure with coordinated strength and toughness control according to claim 3 is characterized in that: In the step S1, a two-phase bionic Bouligand structure sample is prepared by molten filament printing. The sample is printed by a dual-nozzle printer. The left and right nozzles of the printer print different materials simultaneously, and finally a two-phase bionic Bouligand structure is manufactured.

5. The bionic dual-phase design method for a metamaterial structure with coordinated strength and toughness control according to claim 3 is characterized in that: The steps of experimental verification in step S3 include: S31A, 3D modeling and molten filament manufacturing of the designed configuration; S32A, quasi-static compression, dynamic compression and three-point bending tests were performed on the configuration; S33A, record and export the experimental results required for analysis through the equipment.

6. The bionic dual-phase design method for a metamaterial structure with coordinated strength and toughness control according to claim 3 is characterized in that: The steps of performing numerical simulation verification in step S3 include: S31B, obtain the material parameter constitutive model of the soft and hard dual-phase materials; for the quasi-static compression model, the material needs to be subjected to a uniaxial tensile test, and the material constitutive model used in the dynamic compression model needs to be subjected to a dynamic mechanical analysis of the material; S32B, perform 3D modeling and meshing of the configuration under different working conditions of quasi-static compression, dynamic compression and three-point bending, and set appropriate boundary conditions; S33B, calculate and export the results required for the experiment for analysis.

7. The bionic dual-phase design method for a metamaterial structure with coordinated strength and toughness control according to claim 6, characterized in that: The quasi-static compression numerical simulation in step S32B includes: Finite element software is used to simulate its quasi-static compression mechanical behavior. A quasi-static compression geometric model is established, including two rigid platens and a target specimen. Contact is applied between the rigid platens and the target specimen, and a displacement load is applied to the upper rigid platen. The lower rigid platen is fixed, and units are used to discretize the rigid platens and the structural specimen, respectively.

8. The bionic dual-phase design method for a metamaterial structure with coordinated strength and toughness control according to claim 6, characterized in that: The dynamic compression numerical simulation in step S32B includes: Finite element software was used to simulate its dynamic compression mechanical behavior. A full-size SHPB model was established, including the specimen, bullet, incident rod and transmission rod. Contact was imposed between the rigid platen and the target specimen, and velocity load was applied to the bullet. The bullet, incident rod and transmission rod were discretized using units, and the units of the structural specimen were the same as those during quasi-static loading.

9. The bionic dual-phase design method for a metamaterial structure with coordinated strength and toughness control according to claim 3, characterized in that: The step of performing application verification in step S3 includes: S31C, adding a biphasic bionic Bouligand structure into a common insole to design a BDBM insole; S32C, compare and calculate the impact response spectra of BDBM insoles under different parameters; S33C, select the configuration with the best effect, place the PVDF piezoelectric film sensor between the insole and the heel, and record the dynamic real-time signal; S34C, output signal results and analyze them.

Citation Information

Patent Citations

  • High-strength water-resistant chitosan film with structural color and preparation method of high-strength water-resistant chitosan film

    CN113583274A

  • Bionic anti-impact sandwich plate based on Bouligand structure as well as preparation method and application of bionic anti-impact sandwich plate

    CN117621594A

  • A chiral Nitrogen-doped nematic carbon-sheath nanofiber, method for its preparation, and use thereof

    KR102256257B1

Cited By

  • Tough structure additive manufacturing method based on single-material multiple-printing-parameter combination and application of tough structure additive manufacturing method

    CN119858307A